New insight: particle flow rate from the airways as an indicator of cardiac failure in the intensive care unit. (28th November 2022) - Lindstedt, Sandra; Hyllen, Snejana
Abstract: Aims: Exhaled breath particles have been explored for diagnosing different lung diseases. We recently showed in an experimental model that different cardiac output results in different particle flow rate (PFR) from the airways. Given the well‐known close relationship between impaired cardiac function and respiratory failure, we hypothesized that PFR in exhaled air can be used to detect cardiac failure. Methods: PFR was analysed using a customized PExA device. Particles in the range of 0.41–4.55 μm were measured. The included patients ( n = 20) underwent cardiac surgery and received mechanical ventilation as a part of routine post‐operative care. Ten patients with clinical signs of pronounced post‐operative haemodynamic instability and need for inotrope or mechanical support had been selected to the cardiac failure group. The control group consisted of 10 patients without signs of cardiac failure. Results: The patients in cardiac failure group required inotropic support in the form of dobutamine (9/10), epinephrine (2/10), or levosimendan (4/10) or use of an intra‐aortic balloon pump (4/10). There was no use of inotropes or mechanical support devices among the controls. All patients in the cardiac failure group had pre‐operative left ventricular ejection fraction ≤40% compared with the control group, whose pre‐operative ejection fraction was ≥50%, P < 0.001. Patients with cardiac failure had significantly longer median total time in mechanical ventilation compared with the patients in the control group: 53.5 h (IQR 6.8–116101.0 h) and 4.5 h (IQR 4.0–5.5 h), respectively, P < 0.001, and the median length of stay in the ICU, 165 h (IQR 28–192 h) and 22 h (IQR 20–23.5 h), respectively, P = 0.007. Median PFR in patients with cardiac failure was higher than PFR in those with normal cardiac function: 80.9 particles/min (interquartile range (IQR) 25.8–336.6 particles/min), vs. 15.3 particles/min (IQR 8.1–17.7 particles/min), respectively, P < 0.001. Median particle mass was 8.95 ng (IQR 1.68–41.73 ng) in the cardiac failure group and 0.75 ng (IQR 0.18–1.45 ng) in the control group, P = 0.002. Conclusions: Patients with post‐operative cardiac failure following cardiac surgery exhibited an increase in exhaled particle mass and PFR compared with the control group, indicating a significant difference between those two groups. The increase in particle mass and PFR in the absence of respiratory pathologies may indicate cardiac failure. In comparison with controls, impaired cardiac function was also associated with different composition of the particles regarding their size distribution.